Etiology of Breast Implant-Associated Anaplastic Large Cell Lymphoma (BIA-ALCL): Current Directions in Research - Deva, Anand K; Turner, Suzanne D; Kadin, Marshall E; Magnusson, Mark R; Prince, H Miles; Miranda, Roberto N; Inghirami, Giorgio G; Adams, William P (Cancers, 2020)
Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a CD30-positive, anaplastic lymphoma kinase-negative T-cell lymphoma. Where implant history is known, all confirmed cases to date have occurred in patients with exposure to textured implants. There is a spectrum of disease presentation, with the most common occurring as a seroma with an indolent course. A less common presentation occurs as locally advanced or, rarely, as metastatic disease. Here we review the immunological characteristics of BIA-ALCL and potential triggers leading to its development. BIA-ALCL occurs in an inflammatory microenvironment with significant lymphocyte and plasma cell infiltration and a prominent Th1/Th17 phenotype in advanced disease. Genetic lesions affecting the JAK/STAT signaling pathway are commonly present. Proposed triggers for the development of malignancy include mechanical friction, silicone implant shell particulates, silicone leachables, and bacteria. Of these, the bacterial hypothesis has received significant attention, supported by a plausible biologic model. In this model, bacteria form an adherent biofilm in the favorable environment of the textured implant surface, producing a bacterial load that elicits a chronic inflammatory response. Bacterial antigens, primarily of Gram-negative origin, may trigger innate immunity and induce T-cell proliferation with subsequent malignant transformation in genetically susceptible individuals. Although much remains to be elucidated regarding the multifactorial origins of BIA-ALCL, future research should focus on prevention and treatment strategies, recognizing susceptible populations, and whether decreasing the risk of BIA-ALCL is possible.
Keywords: bacterial; breast implants; lymphoma; T-cells; antigens